PS02.162: THREE-YEAR OVERALL SURVIVAL UPDATE FROM PHASE II STUDY OF CHEMOSELECTION WITH DCF AND SUBSEQUENT CONVERSION SURGERY FOR LOCALLY ADVANCED UNRESECTABLE ESOPHAGEAL CANCER. (14th September 2018) - Yokota, Tomoya; Kato, Ken; Hamamoto, Yasuo; Tsubosa, Yasuhiro; Ogawa, Hirofumi; Ito, Yoshinori; Hara, Hiroki; Ura, Takashi; Kojima, Takashi; Chin, Keisho; Hironaka, Shuichi; Kii, Takayuki; et al.
Abstract: Background: A multicenter phase II trial revealed that docetaxel plus 5-fluorouracil and cisplatin (DCF) induction chemotherapy (IC) and subsequent conversion surgery (CS) was tolerable and effective in patients with locally advanced unresectable esophageal cancer (LAUEC) (Br J Cancer 2016;115:1328–1334). Here, we report updated 3-year analyses to further characterize the impact of DCF-IC followed by CS. Methods: Esophageal cancer patients with clinical T4 disease and/or unresectable supraclavicular lymph node metastasis were eligible. The treatment starts with 3 cycles of DCF-IC, followed by CS if resectable, or by concurrent radiation plus chemotherapy with 5-fluorouracil and cisplatin (CF-RT) if not resectable. This updated analysis represents 3-year overall survival (OS), 3-year progression free survival (PFS), location of relapse, and subsequent therapy. Results: As of October 11, 2017, 25 patients were dead. The median follow-up period in patients surviving without death was 39.3 months (95%CI: 38.7 - 41.7months). The estimated 1-year OS was 66.7% and lower limit of 95% confidence interval was 54.6%. The estimated 3-year OS was 46.6% (95% CI; 34.2 - 63.5%). The OS for patients who underwent R0 resection (n = 19) was significantly longer than those who did not undergo R0 resection (3-year OS: 71.4% vs. 30.1%). The estimated 1-year PFS was 50.6% (95%CI: 38.1 - 67.3%) and the estimated 3-year PFS was 39.6% (95%CI: 27.7 - 56.6%). The PFS for patients who underwent R0 resection (n = 19) was significantly longer than those who did not undergo R0 resection (3-year PFS: 61.3% vs. 25%). The recurrence or progression in primary site was observed in 31% of non R0 group. There was no significant difference in the rates of distant metastasis between the two groups (non R0 group vs. R0 group; 21% vs. 16%). The subsequent therapy after protocol therapy included chemotherapy (n = 18), radiotherapy (n = 11), and surgery (n = 5). Conclusion: This longer follow up of DCF-IC followed by CS strategy for patients with LAUEC revealed promising OS and PFS. Based on this phase 2 trial, JCOG1510, a prospective randomized controlled trial to compare chemoselection with DCF-IC followed by CS versus CF-RT as a standard treatment is in preparation for LAUEC. Disclosure: All authors have declared no conflicts of interest.